Penerapan Association Rule Pada Data Persediaan Bahan Baku Di Pro AB Chicken Jambi - Astuti, Reny Wahyuning (Lembaga Penelitian dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2017)
Data Mining is an attempt to extract useful and valuable information on a very large database. The frequent occurrence of a void of raw material inventory for menus often purchased simultaneously by customers is the result of the lack of information about customer spending habits. So it is necessary to extract the information on the transaction data with association rules techniques to know the menu often purchased simultaneously by the customer. Association rules are also often called shopping cart analysis, the algorithm used in association rules in this research is an a priori algorithm with sales menu transaction dataset. The results obtained from data processing sales transaction is a combination item (itemset) with the value of the association of support and confidence value. The information generated is by knowing the most widely sold products then the company can develop strategies by adding raw material inventory. Keywords: Data Mining, Association Rules, Apriori Algorithms, Sales Transactions.